Neuropsychiatric Inventory data in a Belgian sample of elderly persons with and without dementia - Squelard GP (Dove Medical Press, 2012)
Gilles P Squelard,1 Pierre A Missotten,1 Louis Paquay,2 Jan A De Lepeleire,2 Frank JVM Buntinx,2 Ovide Fontaine,1 Stephane R Adam,1 Michel JD Ylieff11Clinical Psychology of Ageing, Qualidem Research Project, University of Liège (ULg), Liège, Belgium; 2KU Leuven, Department of Public Health and Primary Care, Leuven, BelgiumBackground/aims: This study assesses and compares prevalence of psychological and behavioral symptoms in a Belgian sample of people with and without dementia.Methods: A total of 228 persons older than 65 years with dementia and a group of 64 non-demented persons were assessed using the Neuropsychiatric Inventory (NPI) in 2004.Results: Within the group without dementia, the most frequent symptoms were depression, agitation, and irritability. Within the group with dementia, the most common symptoms were depression, irritability, apathy, and agitation. Prevalence of delusions (P < 0.05), hallucinations (P < 0.05), anxiety (P < 0.05), agitation (P < 0.05), apathy (P < 0.01), aberrant motor behavior (P < 0.01), and eating disorders (P < 0.05) were significantly higher in the group with dementia.Conclusion: Depression, elation, irritability, disinhibition, and sleeping disorders are not specific to dementia. Agitation, apathy, anxiety, and delusions are more frequent in dementia but were not specific to the dementia group because their prevalence rates were close to 10% in the group without dementia. Hallucinations, aberrant motor behavior, and eating disorders are specific to dementia. The distinction between specific and nonspecific symptoms may be useful for etiological research on biological, psychological, and environmental factors.Keywords: behavior, behavior disorders, epidemiology, dementia, psychiatric symptoms, neuropsychiatry